2005
DOI: 10.1080/00016480510039995
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of electrode position inside the cochlea for different cochlear implant systems

Abstract: Both Clarion HiFocus I and II electrode arrays were found to be placed close to the inner wall of the cochlea. Ineraid and Med-El Combi40+ electrode arrays were both placed close to the organ of Corti, the Med-El Combi40+ arrays demonstrating the deepest insertions overall. In spite of marked differences in the positions of the contacts, we did not find any correlation with speech perception performance for the different types of implants studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 27 publications
0
19
0
2
Order By: Relevance
“…The measurements of the mean insertion depth of all CI recipients in this study revealed 21.5 mm (SD, 1.1), which demonstrates that the intended depth was well achieved. In terms of estimating the coverage of the cochlear length, the angle of insertion is more meaningful than insertion length, considering that different arrays with similar insertion lengths occupy different positions inside the cochlea (23). Mean insertion angle for all CI recipients was 388 degrees (SD, 34.7) so that cochlear coverage is slightly more than just the basal turn (15).…”
Section: Discussionmentioning
confidence: 99%
“…The measurements of the mean insertion depth of all CI recipients in this study revealed 21.5 mm (SD, 1.1), which demonstrates that the intended depth was well achieved. In terms of estimating the coverage of the cochlear length, the angle of insertion is more meaningful than insertion length, considering that different arrays with similar insertion lengths occupy different positions inside the cochlea (23). Mean insertion angle for all CI recipients was 388 degrees (SD, 34.7) so that cochlear coverage is slightly more than just the basal turn (15).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the Schatzer et al (2014) insertion is similar to other insertions in the field. The 20% trimmed mean insertion of 31 mm MED-EL electrodes from the 8 additional studies (Baumann and Nobbe, 2004; Kos et al, 2005; Hamzavi and Arnoldner, 2006; Gani et al, 2007; Radeloff et al, 2008; Vermeire et al, 2008; Trieger et al, 2011; Landsberger et al, 2015) reported in Table 1 of Landsberger et al (2015) is 627°. We therefore anticipate that collapsing across electrode numbers instead of electrode angles will produce a similar but noisier result than had we collapsed across electrode position.…”
Section: Discussionmentioning
confidence: 99%
“…These "modiolus-hugging" or "perimodiolar" electrodes extend deeper into the cochlea than straight electrodes of the same length. For this reason, in terms of estimating the coverage of the cochlear length, angle of insertion measures are more meaningful than insertion length (Kós et al 2005). Table 1 provides a summary of the dimensions of the electrode arrays from the currently available commercial devices.…”
Section: Electrode Design and Insertion Depthmentioning
confidence: 99%